Electric Field Stimulation of Stem Cell Culture Media Increases Oxygen Radical Uptake Capacity - Maki Yoshikawa; Masatoshi Oshita; Tomomi Gotoh; Yukina Tawa; Katsuaki Dan (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Stem cell culture medium is garnering attention because it comprises growth factors and exosomes secreted by stem cells. In this study, stem cell culture medium was subjected to electric field stimulation using the cells alive system (CAS) to determine the antiaging effects of this medium on dermal fibroblasts.METHODS: The medium was added to the monolayer cultures of human fibroblasts with or without 100 μg/mL advanced glycation end products (AGE), and the cells were incubated for 4 hours. Total RNA was extracted, and mRNA levels of several AGE receptors and heat shock proteins were measured using quantitative reverse transcriptase-polymerase chain rection (qRT-PCR).RESULTS: Similar amounts of exosomes were extracted from the supernatants of stem cells cultured with (CAS+) and without (CAS−) electric field stimulation. The results demonstrated that CAS+ had a higher oxygen radical absorbance capacity than CAS−, indicating its high antioxidant activity. Furthermore, the expression of domain-containing link scavenger receptor-1 mRNA, which is involved in the degradation of cell surface receptors for AGE under glycation stress, significantly increased. The electric field stimulation also increased the expression of several heat shock proteins, which play important roles in cellular responses generated against glycation stress. The electric field stimulation of the stem cell culture medium effectively promoted the endocytosis and degradation of AGE, thereby exerting antioxidant effects and inducing glycation stress.CONCLUSION: Electric field stimulation of stem cell culture medium enhanced the expression of Hsp and its antioxidant activity in fibroblasts.KEYWORDS: AGE, electric field stimulation, exosome, fibroblast, oxygen radical absorbance capacity, stem cell